The political ideas of Thorstein Veblen - Plotkin, Sidney; Tilman, Rick. (New Haven : Yale University Press, 2011)
Thorstein Veblen is best known for his authorship of The Theory of the Leisure Class and The Theory of Business Enterprise, which made him a celebrated figure in the fields of economics and sociology at the turn of the twentieth century. In this book, Sidney Plotkin and Rick Tilman argue that in addition to his well-known work in these fields Veblen also made important--and until now overlooked--statements about politics. While Veblen's writings seldom mention politics, they are saturated with political ideas: about the relationship among war, executive power, and democracy; about the similarities between modern executive positions and monarchy; about the political influence of corporate power; about the symbolism of politics; and about many other issues. By demonstrating the deep relevance of Veblen's writings to today's political troubles, The Political Ideas of Thorstein Veblen offers an important reconsideration of a major American thinker.
Introduction : power and politics in Veblen -- Social science and politics -- The assorted politics of Veblen criticism -- The politics of power and predation -- Savagery and its anarchistic legacies -- Illiberal habits, war, and state formation -- Ostensible democracy -- Veblen and politics : an overview.
Includes bibliographical references (pages 241-264) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Veblen, Thorstein, -- 1857-1929 -- Political and social views; Veblen, Thorstein, -- 1857-1929; Political science -- Philosophy; POLITICAL SCIENCE -- History & Theory; POLITICAL SCIENCE -- Political Economy; Political and social views; Political science -- Philosophy